General characteristics, risk-stratified and sex-stratified clinical outcomes in Bangladeshi people with type 2 diabetes mellitus who fasted during Ramadan 2022: A multicenter, real-world, cross-sectional study - Fariduddin, Md; Khan, Murshed Ahamed; Gaffar, Abu Jar; Alam, Md Jahangir; Akter, Farhana; Hassan, Md Qamrul; Hossain, Md Anowar; Nabi, Md Masud Un; Asaduzzaman, Md; Islam, AHM Shadequl; Sultana, Nusrat; Banu, Hurjahan; et al. (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: Fasting during Ramadan presents both spiritual significance and physiological challenges, particularly for individuals with type 2 diabetes mellitus (T2DM). While previous research has yielded mixed results, there remains a gap in real-world multicenter data on the clinical impact of fasting in risk- and sex-stratified patients with T2DM. Objective: The study aimed to assess the characteristics and clinical and behavioral outcomes among T2DM patients who fasted during Ramadan 2022, stratified by risk using the International Diabetes Federation-Diabetes and Ramadan (IDF-DAR) criteria 2021, and also stratified by sex. Methods: This cross-sectional, multicenter survey was conducted across 14 tertiary hospitals in Bangladesh following Ramadan 2022. Adult patients with T2DM who had fasted for at least 1 day were included and categorized into low-, moderate-, and high-risk groups using the IDF-DAR risk score (2021). Data were collected on demographics, fasting practices, hypoglycemia, glucose monitoring, and clinical parameters, including HbA1c and comorbidities. Results: Of 2,382 screened patients, 2,304 were included and categorized into low-risk (n=231; 10.0%), moderate-risk (n=660; 28.6%), and high-risk (n=1,413; 61.3%) groups according to IDF-DAR 2021 criteria. Hypoglycemia was more frequent among high-risk patients (26.9%) compared to moderate (14.5%) and low-risk (9.5%) groups. Only 53.4% of high-risk individuals received pre-Ramadan counseling, and 29.6% did not self-monitor blood glucose despite clinical indications. Females were more likely to rely on symptoms rather than glucose testing for hypoglycemia detection (64.7% vs. 44.0%; p<0.001). Furthermore, more females believed that blood glucose testing breaks the fast (20.1% vs. 16.3%; p=0.024). Conclusion: While high-risk individuals faced significantly higher rates of hypoglycemia, the majority fasted without adverse outcomes, suggesting that safe fasting may be achievable even in high-risk groups. However, the low rates of pre-Ramadan counseling and the prevalence of sex-specific misconceptions regarding glucose monitoring, particularly among women, reveal critical gaps. Bridging these gaps through tailored, culturally sensitive education is essential to minimize risks and optimize the safety of Ramadan fasting in this vulnerable population. [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 02-11]